The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1126/science.1116994
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Biological Systems as Models for Synthetic Composites

Abstract: Advances that have been made in understanding the mechanisms underlying the mechanical behavior of a number of biological materials (namely mollusk shells and sponge spicules) are discussed here. Attempts at biomimicry of the structure of a nacreous layer of a mollusk shell have shown reasonable success. However, they have revealed additional issues that must be addressed if new synthetic composite materials that are based on natural systems are to be constructed. Some of the important advantages and limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
445
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(459 citation statements)
references
References 18 publications
9
445
0
5
Order By: Relevance
“…Calcium carbonate (CaCO 3 ) is the biomineral phase in many of the highly rigid marine biological structural materials such as the nacre of abalone, conch and other marine mollusks as well as urchin spines and some crustacean exoskeletons [66][67][68][69]. Amorphous CaCO 3 is employed as a precursor to crystalline structures that generally take the form of aragonite (orthorhombic) or calcite (rhombohedral) depending on the growth parameters [68].…”
Section: Biomineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium carbonate (CaCO 3 ) is the biomineral phase in many of the highly rigid marine biological structural materials such as the nacre of abalone, conch and other marine mollusks as well as urchin spines and some crustacean exoskeletons [66][67][68][69]. Amorphous CaCO 3 is employed as a precursor to crystalline structures that generally take the form of aragonite (orthorhombic) or calcite (rhombohedral) depending on the growth parameters [68].…”
Section: Biomineralsmentioning
confidence: 99%
“…This growth has been shown to depend strongly on both nutrient availability and ambient environmental conditions [101]. At quasi-static loading rates in compression, the shells of abalone [66,97,102,103], conch [104,105] and giant clam [96] employ a variety of toughening mechanisms, realized through the brick-and-mortar structure of their nacre, including crack deflection and microbuckling of the calcium carbonate plates to induce a gradual "graceful failure." These toughening mechanisms are imaged in Fig.…”
Section: Mollusk Shellsmentioning
confidence: 99%
“…The current paradigm for designing new composites is that structure, especially "the precise way in which the mineral is arranged in space", matters more than composition when determining properties [3,4]. In most hard biologic tissues such as dentin, enamel, bone, or nacre, the most common feature is a periodic arrangement of the reinforcing mineral phase.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has revealed the mechanism responsible for natural materials' properties and shows that high-performance structural materials could be fabricated via bioinspired strategies. [1][2][3][4][5][6][7][8][9][10] With the quest to develop novel bioinspired materials, it is essential to refine some basic scientific principles that can guide bioinspired fabrication.Recent research has indicated that the amplification of natural materials' mechanical properties far beyond those of the components that comprise them originates mainly from: i) a hierarchical micro-/nanoscale architecture and ii) abundant effective interface interactions. Here, we follow the roadmap of "discovery, invention, and creation," as shown in Figure 1, to give insight into the development of bioinspired structural materials.…”
mentioning
confidence: 99%
“…Extensive research has revealed the mechanism responsible for natural materials' properties and shows that high-performance structural materials could be fabricated via bioinspired strategies. [1][2][3][4][5][6][7][8][9][10] With the quest to develop novel bioinspired materials, it is essential to refine some basic scientific principles that can guide bioinspired fabrication.…”
mentioning
confidence: 99%